Análise histopatológica de fígado de tilápias (Oreochromis Niloticus) expostas ao herbicida 2,4-D comercial - Silva, Mariana Fedocci [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The action of man has led, over the years, major impacts on the environment, especially in aquatic ecosystems, leading to an impairment of water quality, considered one of the essential factors for the maintenance of vital functions and consequently the life of the planet. Among the activities considered a risk for the environment are linked to pollution from many sources and even entire watersheds, whether by industrial waste, sewage, or for substances used in agriculture, such as pesticides, herbicides and fertilizers. The (2,4-D) 2,4- dichlorophenoxyacetic acid is used worldwide, and the fact that its genotoxicity is proven by several studies and by its long persistence in soil, which enables the leaching and percolation of compounds affecting water bodies, toxicity studies are relevant and justifiable. Thus, this study aimed to evaluate the toxicity of 2,4-D by examining the liver of the fish Oreochromis niloticus exposed to different dilutions. Portions of liver were collected and fixed for histological and histochemical techniques to detect total proteins, polysaccharides and lipids. lipids. Treatment with 2,4-D herbicide apparently did not alter the lipid profiles, the accumulation of polysaccharides, and the presence of total proteins. The 2.5 and 5.0% were lethal to fish. These mortalities are probably of high toxic and cytotoxic potential of 2,4-D herbicide results. Several histopathological changes were found, such as: loss of cytoplasmic integrity, loss of cell limit, nuclear deformation, vacuolated cytoplasm, tissue disorganization and hydropic degeneration. Statistically significant changes were: hydropic degeneration and vacuolated cytoplasm. It is concluded, therefore, that the qualitative morphological analysis is an important method for observing changes in liver toxicology studies. As the O. niloticus species is an efficient biological indicator of water pollution by 2,4-D

Ao longo dos anos, a ação do homem tem provocado grande impacto no meio ambiente, principalmente em ecossistemas aquáticos, levando-o ao comprometimento da sua qualidade, uma vez que a água é considerada um dos fatores essenciais para a manutenção das funções vitais e, consequentemente, da vida do planeta. Entre as atividades consideradas de risco para o meio ambiente, estão as ligadas a poluição de muitos mananciais e até bacias hidrográficas inteiras, seja por resíduos industriais, esgoto doméstico, ou ainda, por substâncias utilizadas na agricultura, tais como pesticidas, herbicidas e fertilizantes. O ácido 2,4- diclorofenoxiacético (2,4-D) é usado em larga escala no mundo todo, e pelo fato de ter uma longa persistência no solo, o que possibilita a lixiviação e a percolação do composto afetando corpos hídricos, estudos de sua toxicidade são relevantes e justificáveis. Desta maneira, este estudo procurou avaliar a toxicidade do herbicida 2,4-D por meio da análise de fígados de peixes Oreochromis niloticus, expostos a diferentes diluições. Porções dos fígados foram coletadas e fixadas para serem analisadas por meio de técnicas histológica e histoquímicas para detecção de proteínas totais, polissacarídeos e lipídios. O tratamento com o herbicida 2,4-D aparentemente não alterou o padrão lipídico, o acúmulo de polissacarídeos e a presença de proteínas totais. As concentrações 2,5 e 5,0% foram letais aos peixes. Tais mortalidades provavelmente são resultados do alto potencial tóxico e citotóxico do herbicida 2,4-D. Foram encontradas diversas alterações histopatológicas, sendo elas: perda da integridade citoplasmática, perda do limite celular, deformação nuclear, citoplasma vacuolizado, desorganização do tecido e degeneração hidrópica. As alterações estatisticamente significativas foram: degeneração hidrópica e citoplasma vacuolizado. Concluiu-se, portanto, que a análise...
Keywords: Ecologia aquatica; Histopatologia veterinaria; Tilapia (Peixe); Venenos; Água - Poluição